2021
DOI: 10.1139/cjas-2020-0066
|View full text |Cite
|
Sign up to set email alerts
|

Translactational associations of dry off management, milking activity, and somatic cell count in herds with automated milking systems

Abstract: The objective of this study was to evaluate associations of dry off management factors, milking activity, and production data and somatic cell count prior to dry off and early in the subsequent lactation of cows milked by automated systems. Data were collected for 342 cows from 5 farms, for 2 milk tests prior to dry off and for the 2 milk tests post-calving. The results suggest that the post-calving milking performance of cows milked by automated systems may be more associated with individual cow traits than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Similar to our results, Gott et al (2017) also demonstrated that method of cessation of milking for parlor-milked cows did not influence milk yield in the subsequent lactation. In a similar fashion to our study, Padua et al (2021) demonstrated that postcalving behavior and performance of cows was more likely to be associated with past performance, rather than with the method of dry-off.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Similar to our results, Gott et al (2017) also demonstrated that method of cessation of milking for parlor-milked cows did not influence milk yield in the subsequent lactation. In a similar fashion to our study, Padua et al (2021) demonstrated that postcalving behavior and performance of cows was more likely to be associated with past performance, rather than with the method of dry-off.…”
supporting
confidence: 82%
“…This is consistent with Zobel et al (2013), who demonstrated that parlor-milked cows on either a gradual or abrupt dry-off schedule had similar SCS levels postcalving. However, in a more recent observational study of AMS-milked cows, at the univariable level, cows that were dried off with some type of gradual method tended to have lower SCC after calving compared with cows dried off abruptly (Padua et al, 2021). However, in their multivariable model, those researchers only reported SCC after calving to be associated with SCC before drying off, reaffirming that an important way of promoting low SCC levels after calving is to ensure cows are dried off at a low SCC level.…”
mentioning
confidence: 91%